(untitled) (Revista Latino-Americana de Enfermagem, 2021)
Objective: to evaluate the complications of percutaneous renalbiopsy based on outcomes and clinical indicators of the NursingOutcomes Classification. Method: a prospective longitudinalstudy. The sample consisted of 13 patients submitted topercutaneous renal biopsy, with 65 evaluations. The patientswere evaluated in five moments in the 24 hours after theprocedure, using an instrument developed by the researchersbased on five outcomes (Blood coagulation, Circulation status,Blood loss severity, Pain level, Comfort status: Physical) and11 indicators. The Generalized Estimation Equation Test wasused to compare the scores of the indicators. The project wasapproved by the institutional ethics committee. Results: in the65 evaluations, a statistically significant difference was identifiedin the reduction of the scores of the following nursing outcomes:Blood coagulation, “hematuria” indicator; Circulation status,in the “systolic blood pressure and diastolic blood pressure”indicators and Comfort status: physical, in the “physical wellbeing”indicator. Conclusion: the evaluated patients did notshow major complications. The clinical indicators signaledchanges in circulation status, with reduced blood pressure, aswell as in blood clotting observed by hematuria, but withouthemodynamic instability. The comfort status was affected bythe rest time after the procedure.